EDUCAÇÃO AMBIENTAL VOLTADA À PISCICULTURA PRATICADA POR PEQUENOS PRODUTORES RURAIS - Appolo, Cátia Beatriz; Nishijima, Toshio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
In this paper, it is presented a knowledge investigation that the small farmers, inSapiranga city, have about the fishing they are holding on their properties, and ananalysis, from the point of view of Environmental Education, of the sustainability of thisactivity in the region. Through field research with semi-structured type interviews, thedata survey sought to know the planning and the achievement of fish farming, and toperceive sources of learning, orientation and support. The data showed that thepopulation has important knowledge about the environmental matters and presents aneed for information about environmental impacts and about the environmentallegislation applied to the fish activity. The survey revealed the necessity of specializedtechnical support and subsidies so that the fish activity of the region becomeseconomically feasible. It can be concluded that the notions of citizenship present in theresearched population associated to a multidisciplinary work involving the EnvironmentalEducation will conduct the fish activity of the region to social patterns, economical andecologically sustainable.